Islamic Da‘wah of Wali Songo: Religious Moderation Through Cultural Acculturation in a Pluralistic Society - Mahfudh, Mahfudh; Susetiyo, Ari (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
Abstract The spread of Islam by the Wali Songo in Indonesia is a relevant example of religious moderation, particularly in pluralistic societies. This study aims to analyze the cultural acculturation approach employed by the Wali Songo in their da’wah to promote the formation of an inclusive and tolerant society. A literature study method is used to examine the da'wah strategies of Wali Songo, the concept of cultural acculturation, and its implications for religious moderation. The results show that Wali Songo's da’wah successfully integrated local cultural elements, such as gamelan and wayang, in spreading Islam without requiring the community to abandon their original cultural identities. Their teachings emphasize tolerance, cooperation, and maintaining good relations between religious communities, which are in line with religious moderation principles. In today's increasingly pluralistic society, the inclusive and tolerant values taught by the Wali Songo are crucial for fostering social harmony. Therefore, their teachings, focusing on cultural acculturation and religious moderation, serve as an excellent model for application in Indonesia’s multicultural society. Keywords: Wali Songo, Religious Moderation, Cultural Acculturation. AbstrakPenyebaran Islam oleh Wali Songo di Indonesia merupakan contoh moderasi beragama yang relevan, terutama dalam masyarakat plural. Penelitian ini bertujuan untuk menganalisis pendekatan akulturasi budaya yang dilakukan Wali Songo dalam dakwahnya untuk mendorong pembentukan masyarakat inklusif dan toleran. Metode yang digunakan adalah studi pustaka untuk menganalisis strategi dakwah Wali Songo, konsep akulturasi budaya, serta implikasinya terhadap moderasi beragama. Hasil penelitian menunjukkan bahwa dakwah Wali Songo berhasil mengintegrasikan unsur-unsur budaya lokal, seperti gamelan dan wayang, dalam penyebaran Islam tanpa menghapus identitas budaya asli masyarakat. Ajaran mereka menekankan toleransi, kerja sama, dan menjaga hubungan baik antar umat beragama, sesuai dengan prinsip moderasi beragama. Dalam masyarakat yang semakin plural, nilai-nilai inklusif dan toleransi yang diajarkan Wali Songo sangat penting untuk membangun harmoni sosial. Oleh karena itu, ajaran mereka yang berfokus pada akulturasi budaya dan moderasi beragama dapat menjadi model yang baik untuk diterapkan dalam masyarakat multikultural Indonesia. Kata kunci: Wali Songo, Moderasi Beragama, Akulturasi Budaya.